Anti-thrombotic therapy in patients with atrial fibrillation and intracranial hemorrhage - Diener, Hans-Christoph; Stanford, Sophia; Abdul-Rahim, Azmil; Christensen, Louisa; Hougaard, Kristina Dupont; Bakhai, Ameet; Veltkamp, Roland; Worthmann, Hans (Expert review of neurotherapeutics, 2014)
Patients with atrial fibrillation have an increased risk of ischemic stroke that can be dramatically lowered by treatment with anticoagulants. The annual rate of major bleeds with warfarin averages about 2%. The rates of intracerebral and intracranial bleeds are significantly reduced with the use of the novel direct oral anticoagulants (DOACs) compared with warfarin. Treatment of anticoagulation-related intracerebral hemorrhage is based on the results of case series and small trials. Resumption of anticoagulation in patients with atrial fibrillation who had an intracerebral bleed depends on the etiology and location of the bleeding and the absolute rate of stroke in the absence of anticoagulation.